2008
DOI: 10.7124/bc.0007c1
|View full text |Cite
|
Sign up to set email alerts
|

Somaclonal variability of Ungernia victoris: the necessity of comprehensive genetic analysis

Abstract: An analysis of five 10-year-old U. victoris cell lines of common origin revealed mixoploidy, significant level of cell polyploidization, quantitative and qualitative changes in individual RAPD-fragments. No regularity was observed in the lines clustering depending on the nutrient medium phytohormone composition or genealogy of the lines. The cytogenetic, molecular and genetic approaches are recommended to ensure reliable determination of somaclonal changes, because the variations in ploidy levels do not always… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…9.8 and 9.11). On the whole, our results are consistent with the data available in the literature, indicating that most genome rearrangements occur in the course of dedifferentiation during the early steps of culture in the formation of a stable cell population in vitro (Kunakh 2005;Kuznetsova et al 2005;Bublyk et al 2008;Andreev et al 2009). It is known that an increase in number of passages and their duration may increase the occurrence and rate of somaclonal variation in the callus (Bairu et al 2011).…”
Section: Dependence On the Duration Of Culturesupporting
confidence: 82%
See 2 more Smart Citations
“…9.8 and 9.11). On the whole, our results are consistent with the data available in the literature, indicating that most genome rearrangements occur in the course of dedifferentiation during the early steps of culture in the formation of a stable cell population in vitro (Kunakh 2005;Kuznetsova et al 2005;Bublyk et al 2008;Andreev et al 2009). It is known that an increase in number of passages and their duration may increase the occurrence and rate of somaclonal variation in the callus (Bairu et al 2011).…”
Section: Dependence On the Duration Of Culturesupporting
confidence: 82%
“…According to other data, the level of genetic changes during the early stages of culture may be low but then increase with the duration of culture. For example, using RAPD-PCR and ISSR-PCR, it was demonstrated that long-term culture of Ungernia victoris may result in increased genetic distances between donor plant and lines of callus, as well as divergence of the latter (Bublyk et al 2008(Bublyk et al , 2010.…”
Section: Dependence On the Duration Of Culturementioning
confidence: 99%
See 1 more Smart Citation
“…On the whole, our results are consistent with the data available in the literature, indicating that most genome rearrangements occur in the course of dedifferentiation during the early steps of culture in the formation of a stable cell population in vitro Kuznetsova et al 2005;Bublyk et al 2008;Andreev et al 2009). In particular, PCR analysis showed that callus of G. pneumonanthe and G. lutea underwent detectable changes during the early stages (prior to 6 months).…”
Section: Dependence On the Duration Of Culturesupporting
confidence: 92%
“…In particular, PCR analysis showed that callus of G. pneumonanthe and G. lutea underwent detectable changes during the early stages (prior to 6 months). For example, using RAPD-PCR and ISSR-PCR, it was demonstrated that long-term culture of Ungernia victoris may result in increased genetic distances between donor plant and lines of callus, as well as divergence of the latter (Bublyk et al 2008(Bublyk et al , 2010). 9.8 and 9.11).…”
Section: Dependence On the Duration Of Culturementioning
confidence: 99%